Deficiency of zebrafish fgf20a results in aberrant skull remodeling that mimics both human cranial disease and evolutionarily important fish skull morphologies. Issue 6 (November 2013) - Cooper, W. James; Wirgau, Rachel M.; Sweet, Elly M.; Albertson, R. Craig
SUMMARY The processes that direct skull remodeling are of interest to both human‐oriented studies of cranial dysplasia and evolutionary studies of skull divergence. There is increasing awareness that these two fields can be mutually informative when natural variation mimics pathology. Here we describe a zebrafish mutant line, devoid of blastema (dob), which does not have a functional fgf20a protein, and which also presents cranial defects similar to both adaptive and clinical variation. We used geometric morphometric methods to provide quantitative descriptions of the effects of the dob mutation on skull morphogenesis. In combination with "whole‐mount in situ hybridization" labeling of normal fgf20a expression and assays for osteoblast and osteoclast activity, the results of these analyses indicate that cranial dysmorphologies in dob zebrafish are generated by aberrations in post‐embryonic skull remodeling via decreased osteoblasotgenesis and increased osteoclastogenesis. Mutational effects include altered skull vault geometries and midfacial hypoplasia that are consistent with key diagnostic signs for multiple human craniofacial syndromes. These phenotypic shifts also mimic changes in the functional morphology of fish skulls that have arisen repeatedly in several highly successful radiations (e.g., damselfishes and East‐African rift‐lake cichlids). Our results offer the dob/fgf20a mutant as an experimentally tractable model with which to examine post‐embryonic skull development as it relates to human disease and vertebrate evolution.